2020
DOI: 10.1016/j.eng.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Triazavirin Therapy for Coronavirus Disease 2019: A Pilot Randomized Controlled Trial

Abstract: No therapeutics have been proven effective yet for the treatment of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To assess the efficacy and safety of Triazavirin therapy for COVID-19, we conducted a randomized, double-blinded controlled trial involving hospitalized adult patients with COVID-19. Participants were enrolled from ten sites, and were randomized into two arms of the study with a ratio of 1:1. Patients were treated with Triazavirin 250 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 9 publications
0
47
1
6
Order By: Relevance
“…Triazavirin acts via inhibition of RNA-dependent RNA polymerase enzyme, thereby inhibiting viral RNA synthesis. 132 In their study, Wu et al (2020) found that patients administered triazavirin required fewer respiratory, cardiac, hepatic, or renal support therapies than the control group. 132 However, despite the possible benefit observed, a large randomized, controlled clinical trial is needed before the place of triazavirin can be determined in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triazavirin acts via inhibition of RNA-dependent RNA polymerase enzyme, thereby inhibiting viral RNA synthesis. 132 In their study, Wu et al (2020) found that patients administered triazavirin required fewer respiratory, cardiac, hepatic, or renal support therapies than the control group. 132 However, despite the possible benefit observed, a large randomized, controlled clinical trial is needed before the place of triazavirin can be determined in COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Favipiravir 1600 mg twice on day 1, then 600 mg twice daily for 10-days 2. Umefovir 200 mg three times daily for 7-days FVR compared to Umifenovir did not significantly improve the patient’s recovery Chen et al, 2020 128 ChiCTR20000300001 52 Hospitalized patients with moderate COVID-19 Triazavirin A Pilot Randomized Multicenter Controlled Clinical Trial Triazavirin 250 mg versus a placebo three or four times a day for 7- days Triazavirin group required Fewer therapies for respiratory, cardiac, renal, hepatic, or coagulation supports Wu et al, 2020 132 NCT04315480 100 Hospitalized patients with severe COVID-19 TCZ Off-Label, Non-Randomized, Single-Center Study TCZ 8mg/Kg twice daily IV TCZ significantly reduced the need for mechanical ventilation, duration of hospital stays Toniati et al, 2020 150 63 Hospitalized patients with severe COVID-19 TCZ A Prospective Open, Single-Arm Multicentre Trial TCZ 8 mg/Kg IV or 324 mg SC TCZ improve respiration in a patient with severe COVID-19 Sciascia et al, 2020 151 NCT04346355 126 Hospitalized patients with severe COVID-19 TCZ Prospective, Open-Label, Randomized Clinical Trial TCZ 8 mg/Kg up to a maximum of 800 mg IV TCZ did not improve disease progression compared with standard care Salvarani et al, 2020 169 EudraCT 2020–001934-37 85 Hospitalized patients with severe COVID-19 Methylprednisolone Partially Randomized, Open-Label, Multicenter Controlled Trial 400 mg twice daily for 3-days, then 20 mg twice daily for 3-day...…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that Favipiravir did not have any dramatic efficiency against COVID-19 even at high concentration. Cai et al [ 117 ] conducted an Open-Label Controlled trial to test the efficacy of Favipiravir compared to Lopinavir (LPV)/Ritonavir (RTV) as anti-COVID-19 agents. Patients were randomly allocated to Favipiravir group (dose 1.6 g twice a day for the 1st day; dose 0.6 g twice a day for 2–14 days) and LPV/RTV group (dose 0.4 g/0.1 g twice a day); the results showed that the Favipiravir group patients exhibited higher efficacy than the LPV/RTV group.…”
Section: Favipiravirmentioning
confidence: 99%
“…Favipiravir and umifenovir are broad antivirals approved in countries outside the USA that were used as anti-influenza agents. Both drugs have had limited clinical data supporting their use, although there has been some in vitro data [ 40 , 42 , 95 , 96 ]. Sofosbuvir/daclatasvir is a treatment for hepatitis C infection that has also been found to bind to SARS-CoV-2 [ 97 ].…”
Section: Treatment Optionsmentioning
confidence: 99%